Comparison of Viral Loads in Patients with Co-infections vs. Single-virus Infections. (4th October 2017) - Beveridge, Stockton; Piya, Bhinnata; Stewart, Laura; Lindegren, Mary Louise; Markus, Tiffanie; Schaffner, William; Halasa, Natasha B
Abstract: Background: Molecular testing for respiratory viruses in clinical practice is common, often with multiple viruses detected. Viral load has been correlated with illness severity, but correlation of co-detection of viruses and viral load is less clear. We sought to compare cycle threshold (Ct) values, a marker inversely related to viral load, between single vs. co-detection of common respiratory viruses. Methods: Children <18 years with respiratory symptoms and/or fever who presented to the ED or were admitted were enrolled. Nasal/throat specimens were obtained and combined. Singleplex qRT-PCR was used to test for 11 respiratory viruses. Clinical and demographic information were collected. Results: From 11/15/15-7/15/16, 1255 children were enrolled, with median age of 26.5 months, 53.4% male, 54.3% White, 38.7% Black, 6.4% other, and 23.5% Hispanic. The median days of illness were 3 days. Of the total cohort, 904 (72%) tested positive for at least one viral pathogen. Table 1 compares Ct values of single vs. co-detection for each individual virus. Conclusion: Single detection with RSV, HRV, AdV, and PIV had lower Ct values, indicating higher viral loads, compared with co-detection with other viruses. Additional research is needed to understand the reason for lower viral loads for co-detection vs. single detection in select respiratory viruses. Disclosures: W. Schaffner, Pfizer: Scientific Advisor, Consulting fee. Merck: Scientific Advisor, Consulting fee. Novavax: Consultant, Consulting fee. Dynavax: Consultant, Consulting fee. Sanofi-pasteur: Consultant, Consulting fee. GSK: Consultant, Consulting fee. Seqirus: Consultant, Consulting fee. N. B. Halasa, sanofi pasteur: Research Contractor, Research support. Astra Zeneca: Research Contractor, Grant recipient.